Development of 126Sn separation method by means of anion exchange resin and gamma spectroscopy. (May 2017) - Dulanská, Silvia; Remenec, Boris; Bilohuščin, Ján; Mátel, Ľubomír; Bujdoš, Marek
Abstract: This paper describes a method employing anion exchange resin for determination of 126 Sn in radioactive waste. The method is suitable for the separation of 126 Sn isotope from hydrochloric and hydrofluoric acid solution. The separation is based on precipitation of tin with ammonium sulfide in 0.5 mol L −1 HCl, dissolution of the precipitate in concentrated HCl, loading in 2 mol L −1 HCl onto anion exchange resin column and elution with 2 mol L −1 HNO3 . 126 Sn was measured by gamma spectrometry. Highlights: A method for 126 Sn determination by using anion exchange resin was tested. The influence of HCl and HF acids and stable tin carrier on 113 Sn separation on anion exchange resin was investigated. 126 Sn in evaporator concentrate and sludge samples from nuclear power plants was analyzed.